Evaluating the effectiveness of community health worker interventions on glycaemic control in type 2 diabetes mellitus: a systematic review and meta-analysis - Joseph Evans; Howard Ha; Patrick Thomas White (BMJ Open)
Objective Community health worker (CHW) interventions in control of HbA1c levels in diabetes have shown varied effects in randomised controlled trials. In the systematic review reported here, we aimed to evaluate the independent effectiveness of CHW interventions on the control of HbA1c levels in adults with type 2 diabetes.Design Systematic review and meta-analysis.Participants 1684 participants from 7 studies were included.Interventions Randomised controlled trials of adults with type 2 diabetes receiving CHW interventions of at least 12 months’ duration compared with usual care were eligible. Databases searched were Ovid MEDLINE, the Cochrane Central Register, CINAHL and Web of Science from 2000 to March 2025. Quality was assessed using the Cochrane RoB2 tool.Primary outcome measure Through meta-analysis, we calculated the mean weighted difference (MWD) of change in HbA1c level from baseline between groups using RevMan.Results Seven of 86 retrieved studies were eligible. Six studies were suitable for meta-analysis and included 1280 participants. An inverse variance weighted meta-analysis showed a significant improvement in pooled HbA1c level with an MWD of 0.50% (0.28%, 0.71%) in the CHW group (p<0.0001). Outcome heterogeneity was low (I2=21%), and the overall level of certainty was high.Conclusions CHW interventions in type 2 diabetes showed statistically significant and clinically important reductions in HbA1c levels in people from minority ethnic groups on low income.